2013
DOI: 10.1159/000354032
|View full text |Cite
|
Sign up to set email alerts
|

Primary Dermal Melanoma in a Patient with a History of Multiple Malignancies: A Case Report with Molecular Characterization

Abstract: Introduction: Primary dermal melanoma (PDM) is a recently described clinical entity accounting for less than 1% of all melanomas. Histologically, it is located in the dermis or subcutaneous tissue, and it shows no connections with the overlying epidermis. The differential diagnosis is principally made along with that of metastatic cutaneous melanoma. Case Report: A 72-year-old Caucasian woman with a history of multiple cancers (metachronous bilateral breast cancer, meningioma, clear cell renal cell carcinoma, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
1
8
1
Order By: Relevance
“…Breast cancer and skin cancer. Twelve cases of tumors involving the skin and the breast in the same person have been described (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21); in particular, only two cases (11,12) presented the coexistence of squamous cell carcinoma and breast cancer, similarly to our case, which turns out to be the third case report documented since 1980. As discussed by Pastore et al (12), our patient presented a synchronism of a wide squamous cell carcinoma of the right breast synchronous to a right breast cancer.…”
Section: Review Of the Literaturesupporting
confidence: 72%
See 1 more Smart Citation
“…Breast cancer and skin cancer. Twelve cases of tumors involving the skin and the breast in the same person have been described (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21); in particular, only two cases (11,12) presented the coexistence of squamous cell carcinoma and breast cancer, similarly to our case, which turns out to be the third case report documented since 1980. As discussed by Pastore et al (12), our patient presented a synchronism of a wide squamous cell carcinoma of the right breast synchronous to a right breast cancer.…”
Section: Review Of the Literaturesupporting
confidence: 72%
“…Breast carcinoma and nervous system tumors. The association between breast cancer and primitive brain tumor lesions is weak and less frequent (16,48,49).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In 2014, Sidiropoulos et al (7) used a melanoma gene expression-profiling test to demonstrate that, compared with metastatic melanoma, PDM was more commonly associated with a favourable gene expression profile. Apart from the present case report, no reports have shown evidence of BRAF mutations in PDM (4)(5)(6).…”
Section: Discussioncontrasting
confidence: 61%
“…More recently, several studies have revealed the molecular features of PDM (4)(5)(6)(7). Gene mutation analyses in PDM have not found any mutations in the MAPK pathway genes (4)(5)(6).…”
Section: Short Communicationmentioning
confidence: 99%
“…In addition, PK-M2 is subjected to postranslational modifi cations, such as phosphorylation, glycosylation, ubiquitination, nitrosylation, methylation, acetylation, lipidation, and proteolysis, that infl uence its activity. Moreover, it has been described as a nuclear function of PK-M2 where it coactivates catenin to induce cMyc, Glut1, and LDHA, which contribute to the Warburg effect ( 18 ).…”
Section: Cancer Cell Metabolic Reprogrammingmentioning
confidence: 99%